Stigma, shame, and blame experienced by patients with lung cancer: qualitative study. - Chapple, A; Ziebland, S; McPherson, A (2004)
OBJECTIVES: To draw on narrative interviews with patients with lung cancer and to explore their perceptions and experience of stigma. DESIGN: Qualitative study. SETTING: United Kingdom. PARTICIPANTS: 45 patients with lung cancer recruited through several sources. RESULTS: Participants experienced stigma commonly felt by patients with other types of cancer, but, whether they smoked or not, they felt particularly stigmatised because the disease is so strongly associated with smoking. Interaction with family, friends, and doctors was often affected as a result, and many patients, particularly those who had stopped smoking years ago or had never smoked, felt unjustly blamed for their illness. Those who resisted victim blaming maintained that the real culprits were tobacco companies with unscrupulous policies. Some patients concealed their illness, which sometimes had adverse financial consequences or made it hard for them to gain support from other people. Some indicated that newspaper and television reports may have added to the stigma: television advertisements aim to put young people off tobacco, but they usually portray a dreadful death, which may exacerbate fear and anxiety. A few patients were worried that diagnosis, access to care, and research into lung cancer might be adversely affected by the stigma attached to the disease and those who smoke. CONCLUSION: Patients with lung cancer report stigmatisation with far reaching consequences. Efforts to help people to quit smoking are important, but clinical and educational interventions should be presented with care so as not to add to the stigma experienced by patients with lung cancer and other smoking related diseases.